Influence of the Middle Class on Well-being of Older Adults; Procedia - Social and Behavioral Sciences; Vol. 166 : Proceedings of The International Conference on Research Paradigms Transformation in Social Sciences 2014 (RPTSS-2014), 16–18 October 2014, Tomsk, Russia - Spesivtseva A. L. Anna Leonidovna (2015, 2015)
Title screen